Determination of veterinary drug residues, mycotoxins, and pesticide residues in bovine milk by liquid chromatography electrospray ionisation –tandem mass spectrometry - Hajrulai musliu, Zehra; Uzunov, Risto; Jovanov, Stefan; Kerluku, Maksud; Jankuloski, Dean; Stojkovski, Velimir; Pendovski, Lazo; Sasanya, James Jacob (Walter de Gruyter GmbH, 2022)
Abstract Introduction Multi-class and multi-residue analyses are very complex procedures because of the physico-chemical properties of veterinary drug residues and other contaminants. The purpose of the study was to develop an analytical method for the sensitive determination of 69 analytes in bovine milk by liquid chromatography electrospray ionisation–tandem mass spectrometry. Material and Methods Antimicrobial, anabolic hormone, lactone, β-agonist, mycotoxin and pesticide residues were analysed in 120 raw milk samples from different dairy farms in North Macedonia. Stable isotopically labelled internal standards were used to facilitate effective quantification of the analytes. Results The linear regression coefficients were higher than 0.99, the limits of detection ranged from 0.0036 to 47.94 μg/L, and the limits of quantification ranged from 0.053 to 59.43 μg/L. The decision limit values ranged from 0.062 to 211.32 μg/L and the detection capability from 0.080 to 233.71 μg/L. Average recoveries of the analytes spiked in raw milk were in the range of 70.83% to 109%, intra-day coefficient of variation (CV) values from 2.41% to 22.29%, and inter-day CV values from 3.48% to 23.91%. The method was successfully applied in the testing of bovine milk samples. In five samples residues were detected. They were sulfadimethoxine (in two samples), enrofloxacin, tetracycline and oxytetracycline and were at concentrations below the EU maximum residue limit. Conclusion The method is useful for routine testing for this group of chemical hazards in bovine milk.